THE ROLE OF FREEDOM OF EXPRESSION IN THE REALIZATION OF CONSTITUTIONAL STATE - Sunay, Reyhan (European Scientific Journal, ESJ, 2012)
There are various legal, institutional and illegal mechanisms and means for limiting state power. One of these means is constitution. However, any state with a constitution is not a “constitutional state”. The constitution that bears significance for the „constitutional state‟ is a constitution that limits state power and guarantees fundamental rights and freedoms. On the other hand, freedom of expression enjoys a special importance among the fundamental rights and freedoms. Freedom of expression is important for limited state by virtue of its characteristics that allow both public debate and dissident views and opposition. However, in order for freedom of expression to play a positive part in the realization of constitutional state, a number of factors ranging from the constitution to the understanding of state and from normative regulations to judicial dimension are involved. A constitution that adopts the instrumental state approach, is individual-centered and based on pluralism will guarantee freedom of expression. Moreover, only constitutional guarantees are not enough; application should also take place according to these principles and judicial review should be conducted in accordance with the true function of freedom of expression. The true function of freedom of expression involves protection of questioning and critical remarks.